Application perspective of cavity optomechanical system - Sun, Huanying; Liu, Yulong; Li, Tiefu (Frontiers in Quantum Science and Technology, 2023)
Cavity optomechanical systems are demonstrating diverse applications in sensing and transduction, profiting from advances in related theories and experiments, which also promotes quantum research based on them. Here, we first briefly introduce typical applications of cavity optomechanical systems and some of our recent progress in this field and then discuss the potential of cavity optomechanical systems for exploring fundamental questions in quantum theory and the challenges encountered in current developments. Cavity optomechanical systems will play a vital role in quantum computing and quantum information and will enrich the quantum toolbox, particularly in quantum interfaces and quantum memory.